Contribution of Lumbar Spine Pathology and Age to Paraspinal Muscle Size and Fatty Infiltration. Issue 8 (15th April 2017) - Shahidi, Bahar; Parra, Callan L.; Berry, David B.; Hubbard, James C.; Gombatto, Sara; Zlomislic, Vinko; Allen, R. Todd; Hughes-Austin, Jan; Garfin, Steven; Ward, Samuel R.
Abstract : Study Design: Retrospective chart analysis of 199 individuals aged 18 to 80 years scheduled for lumbar spine surgery. Objective: The purpose of this study was to quantify changes in muscle cross-sectional area (CSA) and fat signal fraction (FSF) with age in men and women with lumbar spine pathology and compare them to published normative data. Summary of Background Data: Pathological changes in lumbar paraspinal muscle are often confounded by age-related decline in muscle size (CSA) and quality (fatty infiltration). Individuals with pathology have been shown to have decreased CSA and fatty infiltration of both the multifidus and erector spinae muscles, but the magnitude of these changes in the context of normal aging is unknown. Methods: Individuals aged 18 to 80 years who were scheduled for lumbar surgery for diagnoses associated with lumbar spine pain or pathology were included. Muscle CSA and FSF of the multifidus and erector spinae were measured from preoperative T2-weighted magnetic resonance images at the L4 level. Univariate and multiple linear regression analyses were performed for each outcome using age and sex as predictor variables. Statistical comparisons of univariate regression parameters (slope and intercept) to published normative data were also performed. Results: There was no change in CSA with age in either sex ( P  > 0.05), but women had lower CSAs than men in both muscles ( P  < 0.0001). There was an increase in FSF with age in erector spinae and multifidus muscles in both sexes ( P  < 0.0001). Multifidus FSF values were higher in women with lumbar spine pathology than published values for healthy controls ( P  = 0.03), and slopes tended to be steeper with pathology for both muscles in women ( P  < 0.08) but not in men ( P  > 0.31). Conclusion: Lumbar muscle fat content, but not CSA, changes with age in individuals with pathology. In women, this increase is more profound than age-related increases in healthy individuals. Level of Evidence: 3